Some Perturbation Problems on 2x2 Nonlinear Hyperbolic Conservation Laws (Journal of Partial Differential Equations, 1998)
We study in this paper the perturbation of elementary waves with interactions: overtaking of shock waves belonging to the same characteristic family and penetrating of a shock wave and a rarefaction wave belonging to the different characteristic family for 2 × 2 genuinely nonlinear strictly hyperbolic conservation laws. The entropy solutions for the perturbed problems are obtained by the Glimm's scheme.
Keywords: 2 × 2 genuinely nonlinear strictly hyperbolic conservation laws; perturbed problem; elementary waves with interuction